Advocacy for Women's Rights and Political Empowerment: Raja Ram Mohan Roy's Contribution to Indian Polity - Chaudhary, Pramod Kumar (Integrated Journal for Research in Arts and Humanities, 2022)
Having particular emphasis on women's liberties or empowering women, the paper aims to analyse the evolution or expansion of a socio-religious changes initiated by Raja Ram Mohan Roy in the 18th century. Raja Ram Mohan Roy founded the Bengali as Persian weekly publications Sambad Kaumudi as well as Mirat-ul Akhbar to serve as the foundation for his reformist revolution in India. This paper also emphasises Raja Ram Mohan Roy's contributions in reporting, that he subsequently utilised to communicate with the public or disseminate his contemporary views for India's cultural renewal or modernity. He believed that his nation could not advance socially or economically with knowledge. In order to set the way for socio-religious changes in the nation, he vigorously promoted contemporary education. This paper also attempts to analyse Raja Ram Mohan Roy's challenges in persuading the public to support women's education or the outlawing of cruel practises like sati. Roy was the driving force behind giving women more control over their lives as well as securing their honourable place in society. He established the Brahmo Samaj in 1829 in an effort to extend the support for his socio-religious reformation agenda.